Replacement Of Fish Meal With Processed Poultry Offal Meal And Soybean Meal In The Diets Of Snakehead, Channa Striata (Bloch, 1793) Juvenile - Mustapar, Nurul Nadiah (2017)
This study was conducted to evaluate the feasibility of lab processed poultry offal meal (P-POM) and soybean meal (SBM) alone and a lab processed and soybean meal combination as a replacement for fish meal (FM) to promote growth and survival in snakehead, Channa striata juveniles. A series of three experiments were conducted, firstly, the replacement of fish meal with lab processed poultry offal meal, secondly, replacement of fish meal with soybean meal and followed by a combination between lab processed poultry offal meal and soybean meal in a fish meal based diet for snakehead juveniles. In the first and second study, fish (mean initial weight, 13 g) were reared in 30 fiberglass tanks (500l) and fed with ten isonitrogenous (40% crude protein) and isocaloric (18.90kJ/g gross energy) diets in triplicates.